Update of the Xylella spp. host plant database – Systematic literature search up to 31 December 2023 - European Food Safety Authority (EFSA); Vincenzo Cavalieri; Elisa Fasanelli; Davide Gibin; Alicia Gutierrez Linares; Pierfederico La Notte; Luca Pasinato; Alice Delbianco (EFSA Journal, 2024)
Abstract This scientific report provides an update of the Xylella spp. host plant database, aiming to provide information and scientific support to risk assessors, risk managers and researchers dealing with Xylella spp. Upon a mandate of the European Commission, EFSA created and regularly updates a database of host plant species of Xylella spp. The current mandate covers the period 2021–2026. This report is related to the 10th version of the database published in Zenodo in the EFSA Knowledge Junction community, covering literature published from 1 July 2023 up to 31 December 2023, and recent Europhyt outbreak notifications. Informative data have been extracted from 39 selected publications. Sixteen new host plants, five genera and one family were identified and added to the database. They were naturally infected by X. fastidiosa subsp. fastidiosa or unknown either in Portugal or the United States. No additional data were retrieved for X. taiwanensis, and no additional multilocus sequence types (STs) were identified worldwide. New information on the tolerant/resistant response of plant species to X. fastidiosa infection were added to the database. The Xylella spp. host plant species were listed in different categories based on the number and type of detection methods applied for each finding. The overall number of Xylella spp. host plants determined with at least two different detection methods or positive with one method either by sequencing or pure culture isolation (category A), reaches now 451 plant species, 204 genera and 70 families. Such numbers rise to 712 plant species, 312 genera and 89 families if considered regardless of the detection methods applied (category E).